O rastlinskih imenih na Gorenjskem - Čop, Dušan (Jezik in slovstvo, 1997)
The article refers to several botanical names for which the local people are in the habit of using in nearly every village either a different name or name-form. The author wishes to remind of wrong use of some these names and anme-forms respectively in the articles published years ago in the natural-science periodical Proteus.
Keywords: Slovene; slovenščina; onomastics; onomastika; rastlinska imena; Upper Carniola; Gorenjska; leksikologija; lexicology; dialectology; dialektologija